Reenvisioning Migration Governance: from Securitization to Talent Exchange Between Nigeria and Lithuania - Žilvinas Švedkauskas (Politologija, 2025)
This article seeks to answer how civil society actors co-opt and navigate external migration governance agendas and vocabularies. Reassessing the so-called liberal migration governance paradox, it presents a case study of the “Digital Explorers” pilot initiative, aimed at fostering legal migration between the European Union and West Africa. By using publicly available and internal project documentation, the article investigates how the project consortium, led by civil society actors, deployed evolving strategies to advocate for migration openness between Lithuania and Nigeria. The study concludes by presenting a taxonomy of rhetorical frames and reflects on its implications for future research on legal migration frameworks between West Africa and EU-13 countries.